Optimal Fertility Decisions in a Life Cycle Model - Ray Rees; Sebastian Scholz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
This model is the first to solve for the optimal timing of childbirth and number of children in a continuous time framework simultaneously. The model depicts how changes in wage at different stages of an individual's life influence the timing decision of childbirth and the optimal number of children. When a woman wants to have more children, she decides to have them at a younger age. Medical research that extends the fecund life span induces women to have fewer children. A reduction of the parental leave due to daycare centers or a reduction in the costs of leave due to child benefits increase the number of children. Women value labour more, when they face the risk of an unknown divorce. This paper also shows that divorce does not change the timing of childbirth directly, it influences the number of children negatively and the reduced number of children delays the timing. The model can be used to predict upper bound fertility rates, when the expected divorce rate continues to increase.
urn:nbn:de:bvb:19-epub-11316-4
Keywords: D12; J13; 330; Fertility; Timing of Childbirth; Number of Children; Fertilität; Familienökonomik; Zeitpräferenz; Weibliche Arbeitskräfte; Lohn; Kinderbetreuung; Lebensverlauf; Theorie